FRUITS AND VEGETABLES MARKET HALL LOCATION SELECTION BY USING INTERVAL-VALUED TRAPEZOIDAL FUZZY GREY RELATIONAL ANALYSIS: AN APPLICATION FOR ISTANBUL - Bilişik, Özge Nalan; Tuzkaya, Umut Rıfat; Baraçlı, Hayri; Tanyaş, Mehmet (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In urban areas, effectively delivering the necessary products for people to survive to the desired points has a vital importance. Determining the urban distribution centers locations truly, which have an important role in distribution networks, will satisfy determining the number of vehicles, minimizing the traffic congestion by determining the routes of vehicles correctly and thus decreasing the environmental effects like noise and emission. In this study, fresh fruits and vegetables market hall (F&VMH), which is an important urban distribution center type that fulfills the food requirements of city residents, location determination problem is investigated. To solve this problem, interval-valued trapezoidal fuzzy grey relational analysis (GRA) method is used because is suitable to deal with poor, incomplete, and uncertain information. When the results are analyzed, it is seen that F&VMHs have to be located in the district which is closer to producers and which has the lower building and land costs.